The end of the line for today's wind turbines. Issue 3 (May 2016) - Kolios, Athanasios; Martínez-Luengo, María
Abstract : We need to start thinking today about the future of our wind turbines, according to Dr Athanasios Kolios and María Martínez-Luengo from Cranfield University.